Thoughts of M. Quraish Shihab On Adornment (Zinah) In Tafsir Al-Misbah - Zahro, Fatimatus; Fathiyaturrahmah; Siti Masrohatin (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Adornment is something that is inherent in women. This can be seen from how they dress, there are a lot of models of women's clothing, therefore every day the clothes that women wear are always different. The trend of adornment and dressing is increasingly in demand today, both from social media and other media. And this has led to different ways of adornment and dressing people from ancient times and now. Also in this day and age, women also work and groom women with beautiful and attractive appearances.this research aims to find out how to adorn that women do when working. In this study, the maudu'i/thematic method was used, while the type of research used was library research and the approach used was qualitative approach. The result of this study is that adornment according to M. Quraish Shihab is not excessively adorned, not tabarruj, walking without swinging, not cursing perfume that smells strong. Adornment that women do when working adornment to Quraish Shihab is permissible as long as they do not adorn excessively, and do not fall into tabarruj and maintain Islamic manners.